Functional thoracic hyperkyphosis model for chronic subacromial impingement syndrome: An insight on evidence based “Treat the Cause” concept – A case study and literature review - Nagarajan, M.; Vijayakumar, P. (IOS Press, 2013)
Recent evidences suggest functional thoracic hyperkyphosis (FTH) could be a different approach in the management of subacromial impingement syndrome (SIS). This case study aims firstly with the development of evidence informed FTH model for SIS. Secondly this study aimed to develop well defined multimodal physical therapy intervention for FTH and its related mechanical consequences in elderly patient with chronic SIS. As a result, Level IV positive evidence was found in both the short and long-term pain and disability of chronic SIS, using FTH model with 26 months of follow-up.